PENGARUH DANA DESA DAN INFRASTRUKTUR TERHADAP KETIMPANGAN PENDAPATAN ANTAR PULAU JAWA DAN SUMATERA - Benardin, Benardin; Anitasari, Merri (Universitas Bengkulu, 2023)
This research aims to determine the effect of village fund and infrastructure variables on income inequality between provinces on the islands of Java and Sumatera. This research uses a quantitative descriptive method, the data used is secondary data, from 2015 - 2021, with a Panel Data regression model analysis tool. Based on the results of research and data processing, the panel data regression results with the best model are the Fixed Effect model, where the village fund variables, national and provincial road infrastructure conditions, electrification ratio and rural household cell phone ownership together have a significant influence on reducing income inequality between provincial governments on the islands of Java and Sumatera. The results of partial statistical tests show that only the rural household cell phone ownership variable has no significant effect in reducing inequality in income distribution between provincial governments on the islands of Sumatera and Java. The implication of this research is that the government must be able to increase the allocation of village funds in the future, prioritize programs and activities for road construction and maintenance so that the quality of the roads is always in good condition and build new roads that produce production. central areas as well as opening village isolation and expanding the reach of electricity services as well as providing Base Transceiver Stations (BTS) to remote villages so that the electrification ratio and use of cellular telephones increases. Keywords: Gini Index, Village Funds, Infrastructure Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh variabel dana desa dan infrastruktur terhadap ketimpangan pendapatan antar provinsi di pulau Jawa dan Sumatera. Penelitian ini menggunakan metode deskriptif kuantitatif, data yang digunakan adalah data sekunder, dari tahun 2015 - 2021, dengan alat analisis model regresi Panel Data. Berdasarkan hasil penelitian dan pengolahan data, hasil regresi data panel dengan model terbaik adalah model Fixed Effect, dimana variabel dana desa, kondisi infrastruktur jalan nasional dan provinsi, rasio elektrifikasi dan kepemilikan ponsel rumah tangga pedesaan bersama-sama memiliki pengaruh yang signifikan dalam mengurangi ketimpangan pendapatan antara pemerintah provinsi di pulau Jawa dan Sumatera. Hasil uji statistik parsial menunjukkan bahwa hanya variabel kepemilikan ponsel rumah tangga pedesaan yang tidak berpengaruh signifikan dalam mengurangi ketimpangan distribusi pendapatan antara pemerintah provinsi di pulau Sumatera dan Jawa. Implikasi dari penelitian ini adalah pemerintah harus dapat meningkatkan alokasi dana desa ke depannya, memprioritaskan program dan kegiatan pembangunan dan pemeliharaan jalan agar kualitas jalan selalu dalam kondisi baik dan membangun jalan baru yang menghasilkan produksi. daerah pusat serta membuka isolasi desa dan memperluas jangkauan layanan kelistrikan serta menyediakan Base Transceiver Station (BTS) ke desa-desa terpencil sehingga rasio elektrifikasi dan penggunaan telepon seluler meningkat. Kata Kunci: Indeks Gini, Dana Desa, Infrastruktur